Hubungan Frekuensi Pemberian Camilan Tidak Sehat dengan Kejadian Stunting pada Balita dengan Edukasi Gizi oleh Tenaga Kesehatan dan Kunjungan Posyandu sebagai Variabel Confounding - Harsono, Rizki Dwi Agustin; Ariesta, Rita; Nurgustiasari, Risa (Consilium Sanitatis: Journal of Health Science and Policy, 2024)
Stunting is a public health issue that reflects chronic malnutrition in toddlers, especially during critical growth periods. This study aims to analyze the relationship between the frequency of unhealthy snack consumption and the incidence of stunting in toddlers. The study employs a cross-sectional design involving 150 toddler respondents and their parents. Data were collected through structured interviews using questionnaires, anthropometric measurements, and observations of unhealthy snack consumption frequency. The results revealed that the prevalence of stunting among toddlers was 18.7%. Additionally, 41.3% of toddlers were frequently given unhealthy snacks more than four times a week. A significant relationship was found between the frequency of unhealthy snack consumption and the incidence of stunting (p < 0.05). The Odds Ratio (OR) value of 3.191 indicates that toddlers frequently consuming unhealthy snacks are three times more likely to experience stunting compared to those who rarely consume such snacks. The analysis of confounding variables, including sources of nutritional information, Pos Pelayanan Terpadu (Posyandu) visits, and family involvement, showed no significant relationship with the incidence of stunting. The conclusion of this study is that excessive consumption of unhealthy snacks is a significant risk factor for stunting. Therefore, the recommendations include enhancing parental education on the importance of nutritious foods, reducing the consumption of unhealthy snacks, and promoting healthy snacks through Pos Pelayanan Terpadu (Posyandu) programs and social media. Further research with a broader scope is suggested to explore other factors influencing stunting in toddlers.